Single haplotype analysis demonstrates rapid evolution of the killer immunoglobulin-like receptor (KIR) loci in primates - Sambrook, Jennifer G.; Bashirova, Arman; Palmer, Sophie; Sims, Sarah; Trowsdale, John; Abi-Rached, Laurent; Parham, Peter; Carrington, Mary; Beck, Stephan (Genome Research, 2005)
The human killer immunoglobulin-like receptors (KIR) are encoded within the Leukocyte Receptor Complex (LRC) on chromosome 19q13.4. Here we report the comparative genomic analysis of single KIR haplotypes in two other primates. In the common chimpanzee (Pan troglodytes), seven KIR genes (ptKIRnewI, ptKIRnewII, ptKIR2DL5, ptKIRnewIII, ptKIR3DP1, ptKIR2DL4, ptKIR3DL1/2) have been identified, and five KIR genes (mmKIRnewI, mmKIR1D, mmKIR2DL4, mmKIR3DL10, mmKIR3DL1) are present in the haplotype sequenced for the rhesus macaque (Macaca mulatta). Additional cDNA analysis confirms the genes predicted from the genomic sequence and reveals the presence of a fifth novel KIR gene (mmKIRnewII) in the second haplotype of the rhesus macaque. While all known human haplotypes contain both activating and inhibitory KIR genes, only inhibitory KIR genes (characterized by long cytoplasmic tails) were found by in silico and cDNA analyses in the two primate haplotypes studied here. Comparison of the two human and the two non-human primate haplotypes demonstrates rapid diversification of the KIR gene family members, many of which have diverged in a species-specific manner. An analysis of the intronic regions of the two non-human primates reveals the presence of ancient repeat elements, which are indicative of the duplication events that have taken place since the last common ancestor.
10.1101/gr.2381205